Elementos para el análisis del mercado en cadena agroindustrial. aplicación al caso de la cadena de la uchuva en la provincia de Sumapaz - Calderon, María Eugenia; Buitrago, Sandra Patricia; Orjuela Castro, Javier Arturo (Revista Científica, 2006)
In this paper it is presented the results of uchuva marketing analysis in the province of Sumapaz, Cundinamarca. It is identified and characterized the principal variables for the analysis of the marketing of uchuva in a competitive context. Finally, based in the characteristics identified, strategies to improvement the competitive are designed.